Fatigue in Medical Residents Leads to Reactivation of Herpes Virus Latency - Uchakin, Peter N.; Parish, David C.; Dane, Francis C.; Uchakina, Olga N.; Scheetz, Allison P.; Agarwal, Neal K.; Smith, Betsy E. (Interdisciplinary Perspectives on Infectious Diseases, 2011)
The main objective of this study was to detect fatigue-induced clinical symptoms of immune suppression in medical residents. Samples were collected from the subjects at rest, following the first night (low-stress), and the last night (high-stress) of night float. Computerized reaction tests, Epworth Sleepiness Scale, and Wellness Profile questionnaires were used to quantify fatigue level. DNA of human herpes viruses HSV-1, VZV, EBV, as well as cortisol and melatonin concentrations, were measured in saliva. Residents at the high-stress interval reported being sleepier compared to the rest interval. EBV DNA level increased significantly at both stress intervals, while VZV DNA level increased only at low-stress. DNA levels of HSV-1 decreased at low-stress but increased at high-stress. Combined assessment of the viral DNA showed significant effect of stress on herpes virus reactivation at both stress intervals. Cortisol concentrations at both stress intervals were significantly higher than those at rest.